Multi‐sequential order transgressive cycles from the last interglacial to the Holocene revealed by deep‐core sediment facies analysis in the Baeksu tidal deposits, south‐west coast of Korea - Serin Lim; Jin Cheul Kim; Dhongil Lim; Yongmi Kim; Tae Soo Chang (The Depositional Record)
Abstract High‐resolution sequence analysis of three drill‐cores with well‐constrained optically simulated luminescence ages reveals a stratigraphic evolution of the Baeksu tidal flat (south‐west coast of Korea) that documents the development of tide‐dominated estuary infill interacting with minimal fluvial processes since marine isotope stage 6. The stratigraphic architecture and its correlation along an upper mudflat‐to‐subtidal transect showcase two different hierarchies of sequences and small‐scale (fifth‐order) subsequences that are nested within larger‐scale (fourth‐order) sequences. Two fourth‐order sequences with a frequency of 100 kyr consist of lower fluvial deposits and overlying tidal deposits, respectively, reflecting a twofold regressive–transgressive sedimentary sequence related to glacial–interglacial cycles. The sequence boundary is marked by an abrupt facies change from oxidised spit gravels (marine isotope stage 3) to tidal muds (marine isotope stage 1). An interesting feature is the presence of two packages of retrograding spit/tidal deposits corresponding to marine isotope stage 5a/b and marine isotope stage 3 interstadials deposited during short‐lived sea‐level rise, in spite of the long‐term phase of glacial sea‐level fall spanning from marine isotope stage 5d to marine isotope stage 2. Identification of deeply oxidised tidal deposits dated to marine isotope stage 5a/b confirms that two short‐term fluctuations in sea level occurred during the long‐lived glacial period. Such nested successions are assigned as fifth‐order subsequences with 40 kyr time intervals. The late Quaternary Baeksu tidal flat succession was thus mainly controlled by two different frequencies and magnitudes of sea‐level changes, associated with major interglacials (marine isotope stage 5e and 1) and minor interstadials (marine isotope stage 5a and 3). More importantly, transgressive episodes are significantly better preserved than regressive phases. This study provides a good example of how multi‐order, multiple transgressive deposition may be preserved in a tide‐dominated estuarine setting, particularly where river inputs are negligible.